Body size and time-to-pregnancy in black women - Wise, Lauren A. (Oxford University Press, 2013)
STUDY QUESTION: Are overall and central obesity associated with reduced fecundability in US black women? SUMMARY ANSWER: Overall and central obesity—based on self-reported measures of body mass index (BMI, kg/m(2)), waist circumference and waist-to-hip ratio—were independent risk factors for subfertility in our cohort. WHAT IS KNOWN ALREADY: Overall obesity (BMI ≥30 kg/m(2)) has been associated with infertility in several studies. The role of central obesity is less clear. There are no previous studies of time-to-pregnancy (TTP) in black women. STUDY DESIGN, SIZE, DURATION: Data were derived from the Black Women's Health Study, a prospective cohort study. During 1995–2011, there were 2239 planned pregnancy attempts reported by 1697 women, resulting in 2022 births. Cohort retention was greater than 80%. PARTICIPANTS/MATERIALS, SETTING, METHODS: Eligible women were aged 21–40 years and reported at least one planned pregnancy attempt during 1995–2011. Height and weight were reported in 1995, with weight updated every two years; waist and hip circumferences were reported in 1995 and updated in 2003. A validation study within the cohort showed high correlations between self-reported and technician-measured weight (r = 0.97), height (r = 0.93), waist circumference (r = 0.75) and hip circumference (r = 0.74). In 2011, TTP was reported in months. Proportional probabilities regression models were used to estimate fecundability ratios (FRs) and 95% confidence intervals (CI), adjusting for covariates. MAIN RESULTS AND THE ROLE OF CHANCE: High BMI was associated with delayed conception: relative to BMI 18.5–24.9, FRs for BMI categories of <18.5, 25.0–29.9, 30.0–34.9 and ≥35.0 were 0.92 (CI: 0.64–1.32), 0.93 (CI: 0.84–1.03), 0.92 (CI: 0.79–1.06) and 0.73 (CI: 0.61–0.87), respectively. Associations were stronger among nulliparous women (P-interaction = 0.003). After controlling for BMI, reduced fecundability was observed among women with large waist circumferences (≥33 versus <26 inches: FR = 0.73, CI: 0.60–0.88) and large waist-to-hip ratios (≥0.85 versus <0.71: FR = 0.83, CI: 0.71–0.97). LIMITATIONS, REASONS FOR CAUTION: TTP was reported retrospectively and error in recall is likely, particularly as time since the pregnancy increases. However, results were similar when based on the most recent versus first pregnancies. Confounding may have been introduced by the lack of control for important determinants of TTP. Nevertheless, control for maternal age and education, which are highly correlated with TTP determinants such as paternal age and persistence in trying, should reduce the extent of confounding. The analysis was confined to planned pregnancies. If pregnancy intention was related both to body size and fecundability, our results could be biased. Bias is likely to be small because we found little difference in body size and other measured characteristics between pregnancy planners and non-planners. WIDER IMPLICATIONS OF THE FINDINGS: Our findings add to the growing body of literature showing that excess BMI is associated with reduced fecundability and further suggest that central obesity is an important independent risk factor for infertility. The relation of obesity to infertility is especially relevant to US black women because they have higher rates of obesity and infertility. Reductions in overall and central obesity may offer the potential to improve fertility outcomes. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by National Cancer Institute grant CA58420. We have no competing interests to report.